Representing Attitudes to Welfare Dependency: Relational Geographies of Welfare. (September 2014) - Pykett, Jessica
This article outlines the recent circulation of media images and discourse relating to characters pre-figured as 'welfare dependents' and reaction to Benefits Street. The article provides a brief overview of sociological analyses of such representations of apparently spiralling 'cultures of dependency' and proposes an alternative relational geography approach to understanding existing welfare dynamics. It describes a shift from putative welfare dependency, to dependency on geographically uneven employment opportunities, low-wage dependency and dependency on a new migrant division of labour. It then contrasts this relational geography approach with the increasingly behaviourist overtones of contemporary welfare reform, which began under New Labour and have accelerated under the Coalition government since 2010. Such policies are in part reliant on the aforementioned media images in securing public acceptance. The article concludes by speculating on the apparent importance of Benefits Street in marking the possible 'end times' for the welfare state as we knew it.